COMPONENTS OF THE INTERNATIONAL MARKETING ENVIRONMENT AND SOCIO-CULTURAL DIMENSIONS OF COUNTRIES’ MARKETS IN THE GEERT HOFSTEDE CONCEPT - Fediv Р.; Fediv І. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The research distinguishes and analyzes the components of international marketing implementation when conducting business activities in foreign markets. The article provides the classification of the environment types. Peculiarities of the environment are considered when developing a complex of measures included in the international marketing complex. The study examines various constituents of the international marketing environment and their relationship with the socio-cultural parameters of the global markets, particularly referring to the Geert Hofstede concept. Apart from that, the specific national patterns of the socio-cultural environment which are particular for the exemplified countries have been researched. They influence the character of cross-cultural communications, in case, when national producers of goods and services reach the markets of those countries or when it is necessary to make some contacts and agreements or have interactions with the residents and other representatives of the business environment, as well as customers of those countries. The article proposes a classification of the types of environments in which international marketing activities are carried out, considering their specific characteristics. The authors examine various factors that influence the formation of a proper environment for effective international marketing. The obtained research results prove the relationship between the components of the international marketing environment and the socio-cultural parameters of the world markets, thus contributing to a better understanding of the impact of socio-cultural factors on international marketing strategies and assisting enterprises in successfully engaging in global markets.